Pengaruh Kepemimpinan, Pelatihan dan Pemberdayaan Terhadap Kepuasan Kerja - Kirana Gita Archia; Hasan Abdul Rozak (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2022)
The purpose of this study was to analyze the influence of leadership, training, and empowerment on job satisfaction of the Semarang City Environment Service's employees. The sample in this study were 102 employees of the Semarang City Environmental Service. Determination of the sample in this study using saturated sampling. The analytical tool used is multiple linear regression analysis. The results of the analysis can be concluded that: Leadership has a positive and significant effect on job satisfaction. Training has a positive and significant effect on job satisfaction. Empowerment has a positive and significant effect on job satisfaction